Akibat Hukum Penolakan Rencana Perdamaian Debitur oleh Kreditur dalam Proses Penundaan Kewajiban Pembayaran Utang - Gede Nira Wicitra Yudha; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2022)
In running a business, there are usually various problems, one of which we often encounter is the problem of accounts payable. This problem usually occurs because one of the parties defaults which causes complex problems that occur, from the point of view of business actors as creditors who want legal certainty regarding their receivables to be paid as soon as possible when they are due, whereas from the customer's point of view as debtors want The debts and receivables were settled amicably, which saw the situation and condition of the debtor's ability to pay without taking assets as collateral for the debt. This then became a factor in the rejection of the reconciliation plan by the creditor in the process of delaying debt payment obligations. The state, in this case policy makers and law enforcers, provides legal certainty to both parties through Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU). The purpose of writing this research is to provide education to the academic community and the public about the legal consequences of rejecting the debtor's reconciliation plan by creditors in the process of delaying debt repayment obligations.